Nitroalkynes: A Unique Class of Energetic Materials - Windler, G. Kenneth; Pagoria, Philip F.; Vollhardt, K. Peter C. (Synthesis, 2014)
Forty-five years after their first preparation, nitroalkynes retain interest for their unique chemical behavior and their potential as energetic materials. This review encompasses the physical and spectral properties, synthesis, reactivity, metal complexes, and theoretical studies of nitroalkynes not previously reviewed, and those prepared after 1973.1 Introduction2 Physical Properties of Nitroalkynes3 Spectral Properties of Nitroalkynes4 Syntheses of Nitroalkynes4.1 Unsuccessful Attempts4.1.1 Nitration4.1.2 Elimination 4.1.3 Retrocycloaddition4.2 Successful Strategies4.2.1 Nitration4.2.2 Elimination 4.2.3 Nucleophilic Displacement4.2.4 From Triazoles4.3 Attempts at the Synthesis of Dinitroacetylene5 Reactions of Nitroalkynes5.1 Thermal Decomposition5.2 Nucleophilic Addition5.3 Cycloaddition6 Metal Complexes7 Theoretical Studies8 Conclusion
Keywords: alkynes; cycloaddition; cycloreversion; nitration; elimination; nucleophilic addition; organic explosives